Dampak Inflasi terhadap Kesenjangan Pendapatan dan Daya Beli Masyarakat di Indonesia - Anggita Mujayanah; Desty Anggraini; Pinkan Dwi Ananda; Rasidah Novita Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Inflation has an impact on income inequality and purchasing power in Indonesia. In recent years, Indonesians have increasingly felt significant economic pressure due to the continuous increase in the prices of goods and services. This research aims to explore the underlying causes of inflation, control efforts, and its impact on people's purchasing power to comprehensively understand Indonesia's inflation dynamics. The method used in this research is a library research approach. Inflation not only affects the value of the currency, but also changes people's spending patterns and purchasing priorities. To overcome this problem, the government implements policies that support the improvement of people's purchasing power and income distribution. This research provides important insights into the interaction between inflation and people's economic conditions, as well as steps that can be taken to create a more stable economic environment.